Occupations and Trades in Catullus’ Poetry - Cerdas Fallas, Maricela (2018)
This paper presents an overview of labor in Ancient Rome and then continues to analyze the mention of different trades in the work of Caius Valerius Catullus, a Roman poet from the I century BC. Catullus mentions, among others, prostitutes, poets, and farmers